Guanosine Tetraphosphate Has a Similar Affinity for Each of Its Two Binding Sites on Escherichia coli RNA Polymerase - Myers, Angela R.; Thistle, Danielle P.; Ross, Wilma; Gourse, Richard L. (Frontiers in Microbiology, 2020)
During nutrient deprivation, the bacterial cell undergoes a stress response known as the stringent response. This response is characterized by induction of the nucleotide derivative guanosine tetraphosphate (ppGpp) that dramatically modulates the cell’s transcriptome. In Escherichia coli, ppGpp regulates transcription of as many as 750 genes within 5 minutes of induction by binding directly to RNA polymerase (RNAP) at two sites ~60 Å apart. One hypothesis for the presence of two sites is that they have different affinities for ppGpp, expanding the dynamic range over which ppGpp acts. We show here that ppGpp has a similar affinity for each site, contradicting that hypothesis. Because the ppGpp binding sites are formed by interactions of the β’ subunit of RNAP with two small protein factors, the ω subunit of RNAP which contributes to Site 1 and the transcription factor DksA which contributes to Site 2, variation in the concentrations of ω or DksA potentially could differentially regulate ppGpp occupancy of the two sites. It was shown previously that DksA varies little at different growth rates or growth phases, but little is known about variation of the ω concentration. Therefore, we raised an anti-ω antibody and performed Western blots at different times in growth and during a stringent response. We show here that ω, like DksA, changes little with growth conditions. Together, our data suggest that the two ppGpp binding sites fill in parallel, and occupancy with changing nutritional conditions is determined by variation in the ppGpp concentration, not by variation of ω or DksA.